The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/su15086929
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Relationship between the Manning Coefficients (n) of a Perforated Subsurface Stormwater Drainage Pipe and the Hydraulic Parameters

Abstract: Subsurface perforated pipes drain infiltrated stormwater runoff while attenuating the peak flow. The Manning roughness coefficient (n) was identified as a fundamental parameter for estimating roughness in various subsurface channels. Hence, in this work, the performance of a six-row non-staggered sand-slot perforated pipe as a sample of the subsurface drainage is investigated experimentally in a laboratory flume at Universiti Sains Malaysia (USM) aimed at determining the Manning roughness coefficients (n) of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Abdullah, Mohd Arif Zainol [36] estimated potential evaporation in Singapore using the Thornthwaite equation [37] based on air temperature, while Qu, Jia [38] used a combination of the Penman equation and the Thornthwaite moisture index for the Singapore climate in their numerical study on the impact of evaporation and infiltration of rainwater on the pore-water pressure changes in a slope of residual soil. These studies showed that the cross-sections of pore-water pressure from seepage analyses by considering rainfall evaporation and infiltration give a sensibly decent concurrence with those acquired from field estimations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Abdullah, Mohd Arif Zainol [36] estimated potential evaporation in Singapore using the Thornthwaite equation [37] based on air temperature, while Qu, Jia [38] used a combination of the Penman equation and the Thornthwaite moisture index for the Singapore climate in their numerical study on the impact of evaporation and infiltration of rainwater on the pore-water pressure changes in a slope of residual soil. These studies showed that the cross-sections of pore-water pressure from seepage analyses by considering rainfall evaporation and infiltration give a sensibly decent concurrence with those acquired from field estimations.…”
Section: Literature Reviewmentioning
confidence: 99%